Effects of Deposition Parameters and Oxygen Addition on Properties of Sputtered Indium Tin Oxide Films - Munir, Badrul; Wibowo, Rachmat Adhi; Ho, Kim Kyoo (Makara Journal of Technology, 2012)
Indium tin oxide (ITO) films were sputtered on corning glass substrate. Oxygen admixture and sputtering deposition parameters were optimized to obtain the highest transparency as well as lowest resistivity. Structural, electrical and optical properties of the films were then examined. Increasing deposition rate and film thickness changed the crystallographic orientation from (222) to (400) and (440), as well as higher surface roughness. It was necessary to apply substrate heating during reposition to get films with better crystallinity. The lowest resistivity of 5.36 x 10-4 Ω•cm was obtained at 750 nm film thickness. The films’ resistivity was increased by addition of oxygen up to 2% in the argon sputtering gas. All films showed over 85% transmittance in the visible wavelength range, possible for applications in photovoltaic and display devices.